Sosialisasi Bahan Insulasi dan Bahan Pendingin Pengganti Es Balok Untuk Para Nelayan di Kabupaten Maros - Syerly Klara; Faisal Mahmuddin (Faculty of Engineering UNHAS, 2023)
Increasing marine resources is one of the main programs of the current government. To support this, it is necessary to increase human resources in coastal areas. One of the very basic and important things is basic knowledge about the cooling process of fish catch on board. The use of ice cubes as a cooling medium for fish that is less than optimal is one of the big problems experienced by fishermen. Their lack of knowledge about the types of refrigerants other than ice cubes results in a loss of fresh catch that reaches consumers as a result they have to spend more money on the cost of buying ice blocks every time they make a voyage. For this reason, in this service program that will be carried out, the community will be guided on the manufacture and treatment of ice gel/packs as a substitute for ice cubes, which is much more effective to use ice gel/packs as a cooling medium which is expected to be able to help fishermen to maintain the quality of their produce. catch and optimize the capacity of the hold space to accommodate more abundant catches to the buying and selling process. This activity will increase the level of productivity and welfare of the fishing community, especially in the place where this activity is carried out, namely in Ampekale Village, Bontoa District, Maros Regency.